2017
DOI: 10.21873/anticanres.12102
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentration of Erlotinib and its Correlation with Outcome and Toxicity in Patients with Advanced-stage NSCLC

Abstract: Erlotinib concentration was not associated with outcome. Erlotinib concentration was associated with occurrence and severity of skin rash and diarrhoea; the outcome was associated with erlotinib toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…9,19 Numerous studies have reported targets or promising candidate C min,ss values for EGFR-TKI and ALK inhibitors (Table 1). [7][8][9][10][11][12][13][14][15][16][17][18][19]21,22 To the best of our knowledge, the present method can be used to determine the concentrations of a greater number of EGFR-TKIs and ALK inhibitors than any other known analytical method for the simultaneous quantification of various TKIs. [23][24][25][26][27][28][29][30][31][32][33][34] The run time of this method is 7 minutes, which is shorter than the run time of a published conventional LC-MS/MS-based method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,19 Numerous studies have reported targets or promising candidate C min,ss values for EGFR-TKI and ALK inhibitors (Table 1). [7][8][9][10][11][12][13][14][15][16][17][18][19]21,22 To the best of our knowledge, the present method can be used to determine the concentrations of a greater number of EGFR-TKIs and ALK inhibitors than any other known analytical method for the simultaneous quantification of various TKIs. [23][24][25][26][27][28][29][30][31][32][33][34] The run time of this method is 7 minutes, which is shorter than the run time of a published conventional LC-MS/MS-based method.…”
Section: Discussionmentioning
confidence: 99%
“…9,19 Numerous studies have reported targets or promising candidate C min,ss values for EGFR-TKI and ALK inhibitors (Table 1). 7–19,21,22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, solid evidence in humans (with the equivalent doses) is missing. At the approved dose, associations between systemic drug exposure and the development of rash and diarrhea have been reported [22,34]. The development of these adverse events was observed to be far less for erlotinib 25-100 mg QD or gefitinib 250 mg on alternating days [24][25][26][27][28][29]35].…”
Section: First-generation Egfr Smismentioning
confidence: 99%
“…For erlotinib, two studies on an E-R relationship have recently been published and these could not identify a relationship between exposure and PFS or OS (resp. in 70 and 122 NSCLC patients) [ 70 , 71 ]. It has been suggested that reduced doses (e.g., 100 or 50 mg/day for erlotinib) could reduce toxicity while maintaining efficacy, especially in frail patients [ 72 , 73 ].…”
Section: Introductionmentioning
confidence: 99%